Introduction: Setting the Stage - Lévesque, Andrée (Madeleine Parent: Activist, 2005)
Portrays Madeleine Parent's life and times.
Keywords: Feminism; History; Parent; Madeleine; 1918-2012; Social conditions; Syndicalism; Women political activists; Working class